Evaluation of pseudo-total and labile metals (Cu, Cr, Ni, Mn, Pb and Zn) in surface sediments at the mouth of tributaries of the Itaipu Reservoir, Brazil - Costa Junior, Ismael Laurindo; Lopes, Thiara Reis; Fonseca, Bruna Ataide Barros; Butik, Mariane; Mees, Juliana Bortoli Rodrigues; Pletsch, Adelmo Lowe; Torres, Yohandra Reyes (Eclética Química, 2018)
Sediments are reservoirs for a variety of substances widely used as indicators of pollution in aquatic environments. In this research was carried out the evaluation of the concentration of metals in the pseudo-total and labile fractions in surface sediments at the mouth of four main tributaries of the Itaipu Reservoir. Three samplings were performed between February 2014 and March 2015 using Petersen type dredger. The determination of metals occurred by atomic absorption spectrometry and physical-chemical parameters by gravimetric and potentiometric techniques. The samples presented neutral to slightly alkaline character and homogeneous pHs. It was observed the predominance of the clay fraction and the occurrence of variable organic matter between the points. In the labile fraction, only the copper content reached concentrations higher than the thresholds effects levels (TEL) at all sampling points. In the pseudo-total fraction, some sites presented for Cr, Pb and Zn TEL level. For Ni, values of probable effects level (PEL) were verified and for Cu, concentrations in severe effect level (SEL) were reported according to the international sediment classification criteria adopted by the National Oceanic and Atmospheric Administration (NOAA).